H2O2 Induces Major Phosphorylation Changes in Critical Regulators of Signal Transduction, Gene Expression, Metabolism and Developmental Networks in Aspergillus nidulans - Ulises Carrasco-Navarro; Jesús Aguirre (Journal of Fungi, 2021)
Reactive oxygen species (ROS) regulate several aspects of cell physiology in filamentous fungi including the antioxidant response and development. However, little is known about the signaling pathways involved in these processes. Here, we report Aspergillus nidulans global phosphoproteome during mycelial growth and show that under these conditions, H2O2 induces major changes in protein phosphorylation. Among the 1964 phosphoproteins we identified, H2O2 induced the phosphorylation of 131 proteins at one or more sites as well as the dephosphorylation of a larger set of proteins. A detailed analysis of these phosphoproteins shows that H2O2 affected the phosphorylation of critical regulatory nodes of phosphoinositide, MAPK, and TOR signaling as well as the phosphorylation of multiple proteins involved in the regulation of gene expression, primary and secondary metabolism, and development. Our results provide a novel and extensive protein phosphorylation landscape in A. nidulans, indicating that H2O2 induces a shift in general metabolism from anabolic to catabolic, and the activation of multiple stress survival pathways. Our results expand the significance of H2O2 in eukaryotic cell signaling.